IPTEK PENGOLAHAN LIMBAH ORGANIK MENJADI BIOKOMPOSER PADA KELOMPOK TANI PADI SRI SUKOREJO PASURUAN - SWASONO, MUH. ANIAR HARI; MUNIR, MISBACH (UNIVERSITAS PGRI MADIUN, 2017)
AbstractProgram IbM aims to 1) Establishing independent farmers in meeting the needs of fertilizer in rice farming, 2) create a technology organic waste treatment based on local resources, 3) Improving the knowledge and ability of farmer groups in production management manufacture bio composer, 4) Increasing awareness group peasants in farming that takes into account the principles of sustainable agriculture, 5) Establish new entrepreneurs that can increase farmers’ income. Target in the program IbM among others: 1) each farmer group has insight and knowledge of manufacturing technology bio composer, 2) each farmer group capable of processing organic waste (livestock manure, hump-banana stems, household organic waste), 3 ) each farmer group is able to manage the business bio composer well, managing of raw material supplies, scheduling, and organizing production capacity, 4) any farmer groups have treatment plants bio composer and its place, 5) any farmer groups can utilize thrasher organic materials, making it easier to cutting-banana stem weevil, vegetables or fruit. The method used in this activity are: 1) Training processing organic wastes into bio composer, 2) demo and facilitation manufacture bio composer together with farmer groups, 3) training and development of production management, 4) Training in the management of the finance, 5) leadership training (leadership) for the management, 6) Develop business into new profitable venture and 7) Making the MOL bio composer installation together with all members of the farmer group partners. The result is 1) Most members of farmer groups (Partner) can range from 90% in the manufacturing process bio composer, 2) Most of the members of farmer groups (Partner) around 85% could be in the process of production management (scheduling, setting raw materials and cooperation in the process of making bio composer, 3) Preparation of installation bio composer in farmers’ groups (partners) have completed 100% and readily used by farmer groups, 4) the Chairman of the farmers’ group has adopted the division of tasks according to their respective division and started making administrative performance reports and financial statements, although still modest. AbstrakProgram IbM ini bertujuan untuk 1) Membentuk petani mandiri dalam pemenuhan kebutuhan pupuk pada usahatani padi, 2) menciptakan teknologi pengolahan limbah organik berbasis sumberdaya lokal, 3) Meningkatkan pengetahuan dan kemampuan kelompok tani dalam manajemen produksi pembuatan biokomposer, 4) Meningkatkan kepedulian kelompok tani dalam berusahatani yang memperhatikan prinsip-prinsip pertanian berkelanjutan, 5) Membentuk wirausaha baru yang dapat menambah pendapatan petani. Target dalam program IbM ini antara lain: 1) setiap kelompok tani memiliki wawasan dan pengetahuan tentang teknologi pembuatan biokomposer, 2) setiap kelompok tani mampu mengolah limbah organik (kotoran ternak, bonggol- batang pisang, limbah organik rumah tangga), 3) setiap kelompok tani mampu mengelola usahabiokomposer dengan baik, mengelola dari kebutuhan bahan baku, penjadwalan, dan mengatur kapasitas produksi, 4) setiap kelompok tani memiliki unit instalasi pengolahan biokomposer beserta tempatnya, 5) setiap kelompok tani dapat memanfaatkan mesin pencacah bahan organik, sehingga lebih mudah dalam pemotongan bonggol-batang pisang, sayur atau buah. Metode pendekatan yang dipakai dalam kegiatan ini adalah: 1) Pelatihan pengolahan limbah organik menjadi biokomposer, 2) demo dan pendampingan pembuatan biokomposer bersama-sama dengan kelompok tani, 3) Pelatihan dan pembinaan manajemen produksi, 4) Pelatihan dalam pengelolaan manajemen keuangan, 5) Pelatihan leadership(kepemimpinan) bagi pengurus, 6) Mengembangkan usaha menjadi usaha baru yang menguntungkan dan 7) Pembuatan instalasi biokomposer MOL bersama- sama dengan seluruh anggota kelompok tani mitra. Hasilnya adalah 1) Sebagian besar anggota kelompok tani (Mitra) berkisar 90% bisa dalam proses pembuatan biokomposer, 2) Sebagian besar anggota kelompok tani (Mitra) berkisar 85% bisa dalam proses manajemen produksi (penjadwalan, pengaturan bahan baku dan kerjasama dalam proses pembuatan biokomposer, 3) Pembuatan instalasi biokomposer di kelompok tani (mitra) sudah selesai 100% dan siap digunakan oleh kelompok tani, 4) Ketua kelompok tani sudah menerapkan pembagian tugas sesuai devisi masing- masing dan mulai membuat administrasi laporan kinerja dan laporan keuangan meskipun masih sederhana.